Математична модель асинхронної машини з несиметрією статора й ротора - Чабан, В.Й.; Чабан, О.В. (Електротехніка і електромеханіка, 2012)
In the paper, a mathematical model of a three-phase induction motor with the stator and rotor unsymmetry is introduced. Differential equations of the electromechanical state are given in real coordinates. Results of computation are presented.